Reflected rather than forward wave pressures account for brachial pressure-independent relations between aortic pressure and end-organ changes in an African community. Issue 10 (October 2015) - Sibiya, Moekanyi J.; Woodiwiss, Angela J.; Booysen, Hendrik L.; Raymond, Andrew; Millen, Aletta M.E.; Maseko, Muzi J.; Majane, Olebogeng H.I.; Sareli, Pinhas; Libhaber, Elena; Norton, Gavin R.
Abstract : Aims: To determine whether brachial blood pressure (BP)-independent relations between aortic pressure and cardiovascular damage are better explained by reflected (backward) (Pb) or forward (Pf) wave pressure effects. Methods: In 1174 participants from a community of African ancestry, we assessed central aortic pulse pressure (PPc), Pb, and Pf (radial applanation tonometry, SphygmoCor) as well as left ventricular mass index (LVMI) ( n  = 786), aortic pulse wave velocity (PWV) ( n  = 1019), carotid intima-media thickness (IMT) ( n  = 578), transmitral early-to-late left ventricular diastolic velocity (E/A) ( n  = 779) and estimated glomerular filtration rate (eGFR) ( n  = 1174). Results: Independent of mean arterial pressure and confounders, PPc, and both Pb and Pf were associated with end-organ measures or damage ( P  < 0.05 to P  < 0.0001). With adjustments for brachial PP and confounders, Pb remained directly associated with LVMI (partial r  = 0.09, P  < 0.01), PWV (partial r  = 0.28, P  < 0.0001), and IMT (partial r  = 0.28, P  < 0.0001), and inversely associated with E/A (partial r  = −0.31, P  < 0.0001) and eGFR (partial r  = −0.14, P  < 0.0001). Similar relations were noted with the presence of end-organ damage ( P  < 0.05 to P  < 0.0001). In contrast, with adjustments for brachial PP and confounders, Pf no longer retained direct relations with LVMI, PWV, and IMT or inverse relations with E/A and eGFR. Adjustments for Pb, but not Pf, diminished brachial PP-independent relationships between PPc and end-organ measures. Independent relations between Pb, but not Pf and end-organ measures, were largely attributed to Pb accounting for most of the variation in brachial-to-aortic PP amplification. Conclusions: In communities of African ancestry, brachial BP-independent relations between aortic pressure and end-organ changes are largely attributed to an impact of reflected rather than forward wave pressures. Abstract : Supplemental Digital Content is available in the text